PORK TRADER PERCEPTIONS AT THE BADUNG MARKET ON THE ELECTION OF SLAUGHTERHOUSE - Kusuma, I Made Gede Wijaya; Agustina, Kadek Karang; Sukada, I Made (Buletin Veteriner Udayana, 2023)
This study aims to determine the perception of pork traders in Badung Market towards the selection of slaughtering sites and to explore the reasons for slaughtering pork at home. All pork traders in Badung Market as many as 38 traders were used as research samples. Data was collected by interviewing pork traders in Badung Market using a questionnaire guide. The data obtained were presented and analyzed descriptively. The results of the research on the perception of pork traders towards pork slaughterhouses in Badung Market showed that from 38 pork traders, 95% of pork traders carried out pork slaughter at RPH and as many as 5% of traders carried out slaughter outside RPH. The cost of slaughtering at the Pesanggaran RPH is IDR 47,500/head and pork traders who carry out the slaughter outside the RPH are subject to a slaughter fee of IDR 100,000/head. The length of the slaughtering process for each pig at the Pesanggaran RPH is ± 2 hours, and the length of the slaughtering process outside the RPH is up to 4 hours. The location of the RPH with traders' houses varies from 4-20 km. However, traders who choose to cut outside the RPH are due to the distance from which they live, which is far from the RPH location. They understand the process of processing RPH waste, and are able to state that the implementation of pork slaughter at the RPH aims to ensure that the pork products they sell are of good quality and are in accordance with applicable regulations so that they are safe for consumer consumption later. Unfortunately, the knowledge and insight possessed by pork traders about RPH, zoonotic diseases and meatborne disease are still lacking. The distance between the location of the traders and the slaughterhouse is the most underlying reason for traders to choose to slaughter their livestock at home. Insufficient knowledge and insight of pork traders will certainly affect the quality of the meat they sell later, it is better to do socialization about RPH, zoonotic diseases and meatborne disease so that pork traders will be able to carry out the correct slaughter and the quality of the meat they sell is guaranteed and very feasible for consumption. In addition, it is also hoped that each district/city must have a RPH that meets the technical requirements set by the ministry of agriculture.